(untitled) (Journal of the College of Basic Education, 2025)
Natural Factors ( geographical location , surface , soil , and climate ) , which are among the basic indicators , contribute to factories fulfilling their vital role in meeting industry requirements . The research aims to test the effectiveness of these factors and the extent of the role they play in the localization of industries within the district and to highlight which of these factors has an impact on the industry .